2007
DOI: 10.1002/cncr.22529
|View full text |Cite
|
Sign up to set email alerts
|

The use of molecular assays to establish definitively the clonality of ipsilateral breast tumor recurrences and patterns of in‐breast failure in patients with early‐stage breast cancer treated with breast‐conserving therapy

Abstract: Clinical classifications of IBTRs were unreliable methods for determining clonality in many patients. Molecular clonality assays provided a reliable means of identifying patients who may benefit from aggressive systemic therapy at the time of IBTR and also provided a more accurate assessment of the efficacy of various forms of local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 43 publications
0
27
1
1
Order By: Relevance
“…Contrary to others (Haffty et al, 1993;Goldstein et al, 2005;Vicini et al, 2007), we found no indication that tumours more prone to be true recurrences because of conserved histological type, location or both, recur sooner or are deadlier than the others. The same applied to the conservation of histological type and features of equal or lesser differentiation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to others (Haffty et al, 1993;Goldstein et al, 2005;Vicini et al, 2007), we found no indication that tumours more prone to be true recurrences because of conserved histological type, location or both, recur sooner or are deadlier than the others. The same applied to the conservation of histological type and features of equal or lesser differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…However, because of the overwhelmingly high rate of the ductal histological type among breast cancers, there is need to improve the definition of true recurrences by using new biological tools of clonal relation such as pan-genomic profiles (Waldman et al, Table 4 Comparison of pathological features of primary tumours and of IBTR according to the free interval between the two (within or after 2 years) , loss of heterozygosity (Schlechter et al, 2004;Vicini et al, 2007), p53 mutation analysis (van der Sijp et al, 2002) or the inactivation of the X chromosome (Shibata et al, 1996). Caution is however still needed as some of these techniques conclude that only 65% of clonally related ipsilateral breast tumour recurrences have the same histological types as their primary tumours (Vicini et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 This study was reviewed and granted approval by the William Beaumont Hospital Human Investigation Committee. Patients with AJCC stage I/II invasive breast carcinoma treated with BCT who developed an IBTR and had no distant metastases (DM) prior to the IBTR were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…La différence entre vraie récidive et nouveau cancer repose actuellement sur des critères mal défi nis, non standardisés. L'utilisation de la biologie moléculaire (génotypage sur fragments de tumeurs congelées [11], technique PCR sur tumeurs « bien techniquées » en paraffi ne [35,67,102]) est actuellement en cours d'évaluation pour essayer de mieux caractériser « vraie RL » et nouveau cancer, à l'aide de biomarqueurs permettant une classifi cation standardisée et reproductible de ces deux entités [75].…”
Section: Dossierunclassified